Site-specific considerations on engineered T cells for malignant gliomas - Elmadany, Nirmeen; Alhalabi, Obada; Platten, Michael; Bunse, Lukas (Biomedicines, 2022)
Immunotherapy has revolutionized cancer treatment. Despite the recent advances in immunotherapeutic approaches for several tumor entities, limited response has been observed in malignant gliomas, including glioblastoma (GBM). Conversely, one of the emerging immunotherapeutic modalities is chimeric antigen receptors (CAR) T cell therapy, which demonstrated promising clinical responses in other solid tumors. Current pre-clinical and interventional clinical studies suggest improved efficacy when CAR-T cells are delivered locoregionally, rather than intravenously. In this review, we summarize possible CAR-T cell administration routes including locoregional therapy, systemic administration with and without focused ultrasound, direct intra-arterial drug delivery and nanoparticle-enhanced delivery in glioma. Moreover, we discuss published as well as ongoing and planned clinical trials involving CAR-T cell therapy in malignant glioma. With increasing neoadjuvant and/or adjuvant combinatorial immunotherapeutic concepts and modalities with specific modes of action for malignant glioma, selection of administration routes becomes increasingly important.